Grant - Chernow, Ron. (New York : Penguin Press, 2017)
"Ulysses S. Grant's life has typically been misunderstood. All too often he is caricatured as a chronic loser and inept businessman, or as the triumphant but brutal Union general of the Civil War. But these stereotypes don't come close to capturing him, as Ron Chernow shows in his masterful biography, the first to provide a complete understanding of the general and president whose fortunes rose and fell with dizzying speed and frequency."--Book jacket.
Introduction: The Sphinx talks -- Part one: A life of struggle. Country bumpkin ; The darling young lieutenant ; Rough and ready ; The son of temperance ; Payday -- Part two: A life of war. The store clerk ; The quiet man ; Twin forts ; Dynamo ; A glittering lie ; Exodus ; Man of iron ; Citadel ; Deliverance ; Above the clouds ; Idol of the hour ; Ulysses the Silent ; Raging storm ; Heavens hung in black ; Caldron of hell ; Chew & choke ; Her satanic majesty ; Dirty boots ; A singular, indescribable vessel -- Part three: A life of peace. Soldierly good faith ; Swing around the circle ; Volcanic passion ; Trading places ; Spoils of war ; We are all Americans ; Sin against humanity ; The darkest blot ; A dance of blood ; Vindication ; A butchery of citizens ; The bravest battle ; Let no guilty man escape ; Saddest of the falls ; Redeemers -- Part four: A life of reflection. The wanderer ; Master spirit ; A miserable dirty reptile ; Taps.
Includes bibliographical references (pages 1021-1031) and index.
Keywords: Presidents -- United States -- Biography; Generals -- United States -- Biography; BIOGRAPHY & AUTOBIOGRAPHY / Military; BIOGRAPHY & AUTOBIOGRAPHY / Presidents & Heads of State; HISTORY / United States / Civil War Period (1850-1877.)